A raisin in the sun - Dee, Ruby; Hansberry, Lorraine, 1930-1965; Hansberry, Lorraine, 1930-1965; McNeil, Claudia; Petrie, Daniel; Poitier, Sidney; Rose, Philip; Susskind, David (RCA/Columbia Pictures Home Video, 1989)
The life of a struggling Black family in a cramped Chicago flat and how it was affected by the promise of a $10,000 life insurance check.